Pengabdian kepada Masyarakat Wonomulyo Tentang Pencegahan Stunting melalui Edukasi Pernikahan Dini dan Pemberdayaan Ekonomi: Service to the Wonomulyo Community Regarding Stunting Prevention through Early Marriage Education and Economic Empowerment - Nurfadilah Maulana S.; Husni Nasir; Abd. Raziq; Ruslang, Ruslang; Hasriani, Hasriani (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The aim of this activity is to provide education to the entire Wonomulyo District community regarding the causes of stunting, the impact of early marriage and economic empowerment. The method used in this activity is the lecture and question and answer method (interactive) between resource persons and seminar participants. The benchmark for the success of this activity uses success indicators, namely participant participation and human resource development. The results of this community service activity show an increase in the scientific insight of the people of Wonomulyo District in minimizing the occurrence of stunting, early marriage and improving the community's economy. The implementation of this activity hopes to reduce the number of early marriages and stunting.